DEVELOPMENT ANDROID-BASED ONLINE LEARNING MEDIA WITH GIF ANIMATIONS AND WHATSAPP APPLICATIONS TO IMPROVE UNDERSTANDING OF BODY ANATOMY SUBJECT MATTER - Rahmat Rahmat; Ansori; Agus Hasbi Noor (Jurnal Empowerment, 2024)
The COVID-19 pandemic is the background for the more extensive development of online learning media used by education in the teaching and learning process. Media and teaching materials are crucial parts of the learning process, especially in online learning. The formulation of the problem in this research is how the development of learning media using WhatsApp and Android GIF animation on the subject of Body Anatomy can be understood by students. The research objective is to find out the development of media and teaching materials on the Body Anatomy subject using WhatsApp media and Android GIF animations. The research was carried out using the R&D method. Online learning media were developed through the validation stage by material experts and media experts. The attractiveness of learning media is based on small-scale trials carried out on 12 students and large-scale trials carried out on 22 students. The test subjects were carried out on 8th grade package B students at PKBM At-Tajdid, Cimahi City. So, the WhatsApp learning media and Android GIF animations that were developed received research in the interesting category and are suitable to be used as learning media for Package B on the Body Anatomy subject.